2004
DOI: 10.1017/s0950268804003206
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of IgA, IgM and IgG antibody-detecting assays based on filamentous haemagglutinin, pertussis toxin and Bordetella pertussis sonicate in a strictly adult population

Abstract: Pertussis diagnosis among adults is primarily based on serology. In this study, receiver operation characteristics (ROC) analysis was utilized to evaluate three IgA, IgM and IgG ELISAs based on B. pertussis whole-cell sonicate (WC), pertussis toxin (PT), or combined PT-filamentous haemagglutinin (FHA) antigens in a healthy adult population and in adults suffering from symptoms consistent with pertussis. The assays were compared to a PT and FHA reference ELISA. The reference assay showed high correlation with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Anti‐PT IgG antibodies respond slower in B. pertussis infection, and the antibody is not raised fully in patients during the acute phase of the disease . A previous report described that the measurement of anti‐PT IgG antibodies remains effective for serum samples taken several weeks after the onset of the disease (coughing) . Additionally, it was shown that the anti‐PT IgG ELISA has high diagnostic accuracy (AUC, 0.96) for convalescent serum samples .…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐PT IgG antibodies respond slower in B. pertussis infection, and the antibody is not raised fully in patients during the acute phase of the disease . A previous report described that the measurement of anti‐PT IgG antibodies remains effective for serum samples taken several weeks after the onset of the disease (coughing) . Additionally, it was shown that the anti‐PT IgG ELISA has high diagnostic accuracy (AUC, 0.96) for convalescent serum samples .…”
Section: Discussionmentioning
confidence: 99%
“…The first was a 15-month (November 2001–March 2003), laboratory-based surveillance study of pertussis, which included 110 trainees who complained of persistent coughing (case definition: cough lasting 10–90 days) upon admission to compound clinics. Samples obtained from these patients were tested by a commercial enzyme-linked immunosorbent assay (ELISA) (PanBio, East Brisbane, Queensland, Australia) for the presence of immunoglobulin (Ig) A against a Bordetella pertussis sonicate and by an in-house IgA-detection ELISA directed against pertussis toxin as previously described ( 9 ). Results for IgA to B. pertussis sonicate were calculated as arbitrary ELISA units obtained according to the manufacturer's instructions.…”
mentioning
confidence: 99%